Injector Quantum Dot Molecule Infrared Photodetector: A Concept for Efficient Carrier Injection - Gebhard, Thomas (Nano-Micro Letters, 2011)
Quantum dot infrared photodetectors are expected to be a competitive technology at high operation temperatures in the long and very long wavelength infrared spectral range. Despite the fact that they already achieved notable success, the performance suffers from the thermionic emission of electrons from the quantum dots at elevated temperatures resulting in a decreasing responsivity. In order to provide an efficient carrier injection at high temperatures, quantum dot infrared photodetectors can be separated into two parts: an injection part and a detection part, so that each part can be separately optimized. In order to integrate such functionality into a device, a new class of quantum dot infrared photodetectors using quantum dot molecules will be introduced. In addition to a general discussion simulation results suggest a possibility to realize such adevice.